DEFECTS IDENTIFICATION OF SOEKARNO-HATTA BRIDGE - Nureksa, Yuda; Suhariyanto, Suhariyanto; Sumardi, Sumardi (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2023)
Soekarno-Hatta Bridge is a bridge that connects Blimbing and Dinoyo Subdistricts, Malang City, as well as an alternative route from Malang City to Batu City. The bridge is 35-year-old, and was built in 1988. The last bridge inspection was carried out in 2014, therefore it is necessary to conduct another inspection to determine the Condition Value of the bridge. By considering the ease of conducting inventory, detailed, and routine inspections, The 2022 National Bridge Inspection Standards (Pedoman Pemeriksaan Jembatan tahun 2022) was used as a reference. Meanwhile, to determine the type of deffect and the Rating Condition of the bridge, the visual analysis method was used. The results of the bridge inspection analysis showed that the Rating Condition of the Soekarno-Hatta steel truss bridge was "1". The number reflects current condition of the bridge that is in a state of minor damage, and the overall condition of the bridge has minor damage and has not expanded. The bridge currently needs indicative maintenance in the form of routine maintenance. From the results of the analysis it was also known that the Rating Condition of the Soekarno-Hatta concrete girder bridge was "2". In a state of moderate damage, an indicative maintenance that should to be done is periodic maintenance.